(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Ethnomathematics is one of various learning approaches within the field of mathematics. It can serve as a bridge connecting mathematics with local culture. This research aims to discover mathematical concepts found in the Javanese calendar system used by the people during the Majapahit era for agricultural activities. This study employs a qualitative approach with a descriptive research method. Data collection was carried out through observation, interviews, and documentation techniques, supplemented by existing literature reviews. The data analysis techniques used were domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. The research results indicate that use of the Javanese calendar system by Majapahit Kingdom society in their agricultural activities contains mathematical concepts within the scope of the least common multiple.